Competition and the single electricity market: Which lessons for Ireland? - Valeria Di Cosmo; Muireann À. Lynch (The Economic and Social Research Institute (ESRI), 2015)
This paper examines the redesign of the Irish Single Electricity Market in order to comply with the European Target Model for electricity. In particular, this work focuses on the challenges raised by the high concentration in the generation sector which exists in the Irish electricity market. We examine the theoretical and empirical conditions under which forward markets promote competition in the spot and retail markets; in addition, we investigate the impact of concentration in the market on the new capacity payment mechanism. In order to ensure a competitive outcome for consumers, the regulatory authorities should continue to regulate the directed forward contracts made by the dominant firm; moreover, our analysis suggests that the regulator should extend regulation to the price and quantity which the dominant firm bids for holding new reliability options.
Keywords: 330; Competition; Forward electricity markets; Capacity payments; Single electricity market